PENINGKATAN KESADARAN MASYARAKAT DALAM MENERAPKAN PERILAKU HIDUP BERSIH DAN SEHAT - Anggi Dwiyanto; Teofilus Ardian Hopeman; Fitriani Setiawan; Areska Areska; Lusi Lusi (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2023)
This community service has been carried out from August to September 2022 in Cikahuripan Village, Cisolok District, Sukabumi Regency. Some of the main problems in Cikahuripan Village are not yet optimal public awareness not to litter, especially throwing garbage in the river. This service aims to increase public awareness of environmental hygiene and health through education and technology. The service is carried out in the form of a seminar entitled